A modified lateral canthal approach for the treatment of zygomatic complex fractures (2014)
We present a modification of the classic lateral canthal approach by means of which the anatomy of the lateral palpebral edges will remain unscathed, with the incision beginning 2 mm lateral to the external canthus. We have used this technique in 76 patients at 3 major trauma centers in Bogota, Colombia, from January 2006 to January 2012. The approach provided excellent access to the frontozygomatic area, lateral wall of the orbit, and malar body. This method avoids important anatomic structures and offers outstanding cosmetic results, especially in adult patients. [ABSTRACT FROM AUTHOR] Copyright of Journal of Oral & Maxillofacial Surgery (02782391) is the property of W B Saunders and its content may not be copied or emailed to multiple sites or posted to a listserv without the copyright holder's express written permission. However, users may print, download, or email articles for individual use. This abstract may be abridged. No warranty is given about the accuracy of the copy. Users should refer to the original published version of the material for the full abstract